Secondary Lymphedema Following Radical Prostatectomy: Noncontrast Magnetic Resonance Lymphangiography Assessment and Vascularized Lymph Node Transfer. Issue 5 (November 2020) - Cellina, Michaela; Martinenghi, Carlo; Gibelli, Daniele; Menozzi, Andrea; Soresina, Massimo; Boccanera, Dario; Giardini, Denisa; Oliva, Giancarlo
Abstract : Abstract: Lymphedema (LE) is a progressive chronic disorder, frequently related to malignancies and their treatment in Western countries. It markedly affected patients' quality of life, and its management is challenging, mainly based on conservative therapy, as bandages and manual lymphatic drainage, with limited results. Recent advances in imaging technology and microsurgical techniques have changed the approach to this disorder, particularly the recent application of magnetic resonance for the study of LE and the increasingly widespread use of surgical interventions, such as vascularized lymph node transfer. As secondary LE due to radical prostatectomy and/or radiation treatment is a frequent cause of chronic disability in the male population, and few data are available in literature about which imaging technique can be applied to diagnose it and about the surgical modalities to treat this condition, we want to propose an overview on the lymphatic vessels anatomy and function, on the applications of noncontrast magnetic resonance lymphangiography and about the pieces of information this examination can provide, and on the technique of vascularized lymph node transfer and the rationale of this surgical procedure in secondary LE related to prostatic malignancy treatment.